Recommendations for somatic and germline genetic testing of single pheochromocytoma and paraganglioma based on findings from a series of 329 patients. Issue 10 (12th August 2015) - Currás-Freixes, Maria; Inglada-Pérez, Lucía; Mancikova, Veronika; Montero-Conde, Cristina; Letón, Rocío; Comino-Méndez, Iñaki; Apellániz-Ruiz, María; Sánchez-Barroso, Lara; Aguirre Sánchez-Covisa, Miguel; Alcázar, Victoria; Aller, Javier; Álvarez-Escolá, Cristina; et al.
Abstract : Background: Nowadays, 65–80% of pheochromocytoma and paraganglioma (PPGL) cases are explained by germline or somatic mutations in one of 22 genes. Several genetic testing algorithms have been proposed, but they usually exclude sporadic-PPGLs (S-PPGLs) and none include somatic testing. We aimed to genetically characterise S-PPGL cases and propose an evidence-based algorithm for genetic testing, prioritising DNA source. Methods: The study included 329 probands fitting three criteria: single PPGL, no syndromic and no PPGL family history. Germline DNA was tested for point mutations in RET and for both point mutation and gross deletions in VHL, the SDH genes, TMEM127, MAX and FH . 99 tumours from patients negative for germline screening were available and tested for RET, VHL, HRAS, EPAS1, MAX and SDHB. Results: Germline mutations were found in 46 (14.0%) patients, being more prevalent in paragangliomas (PGLs) (28.7%) than in pheochromocytomas (PCCs) (4.5%) (p=6.62×10 −10 ). Somatic mutations were found in 43% of those tested, being more prevalent in PCCs (48.5%) than in PGLs (32.3%) (p=0.13). A quarter of S-PPGLs had a somatic mutation, regardless of age at presentation. Head and neck PGLs (HN-PGLs) and thoracic-PGLs (T-PGLs) more commonly had germline mutations (p=2.0×10 −4 and p=0.027, respectively). Five of the 29 metastatic cases harboured a somatic mutation, one in HRAS . Conclusions: We recommend prioritising testing for germline mutations in patients with HN-PGLs and T-PGLs, and for somatic mutations in those with PCC. Biochemical secretion and SDHB-immunohistochemistry should guide genetic screening in abdominal-PGLs. Paediatric and metastatic cases should not be excluded from somatic screening.